Protective effect of afamin protein against oxidative stress related injury in human ovarian granulosa cells - Qiang Zhang; Xiaoyu Zheng; Xueying Zhang; Lianwen Zheng (BMC, 2024)
Abstract Background Ovarian granulosa cells (GCs) play crucial roles in follicular growth and development. Their normal function is influenced by various factors, including oxidative stress, which is a significant factor. Afamin protein is a vitamin E-specific binding protein that acts as a vitamin E carrier in follicular fluid. Although the mechanism of the protective effect of afamin on human ovarian GCs is still unclear, there is evidence it has an antioxidant effect in neuronal cells. Methods In this study, we investigated the protective effects of afamin proteins on testosterone propionate (TP)-induced ovarian GCs using a human ovarian tumor granulosa cell line (KGN). Results The results showed that afamin reduced TP-induced oxidative stress in KGN cells by decreasing the levels of oxidative damage markers, enhancing the activity of antioxidant enzymes, and exerting a protective effect on GCs. Supplementation with afamin repaired mitochondrial dysfunction by improving mitochondrial membrane potential damage and ATP levels. It counteracted TP-induced apoptosis by decreasing the activity of Caspase-3 and upregulating the expression of the anti-apoptotic gene (BCL-2) while downregulating the expression of the pro-apoptotic gene BCL-2-associated X protein (BAX). In addition, afamin regulated the expression of genes related to ovarian steroid hormone synthesis, ameliorating the endocrine dysfunction observed in TP-induced KGN cells. Conclusion Therefore, Afamin proteins may serve as important complementary factors that protect GCs from other types of damage, such as oxidative stress, and may help improve ovarian follicle quality and female reproductive function.